Dome control with fuzzy logic - Castellón, A.; Larrubia, G.; Castillo, R.; Castro-Tirado, A. J.; Fernández-García, E.; Pérez del Pulgar, C.; Reina, A.; Castillo-Carrión, S. (Frontiers in Astronomy and Space Sciences, 2022)
This article describes a fuzzy logic-based method optimized for the dome control of a robotic astronomical observatory. A Mamdani inference has been developed in order to make the decision to open or close the dome. The input variables are obtained from data received from a weather station besides the percentage of cloudy sky as derived by two allsky cameras. The software has been tested at the BOOTES-1 observatory as part of the BOOTES Global Network of Robotic Telescopes led by IAA-CSIC.